2015
DOI: 10.1093/cid/civ486
|View full text |Cite
|
Sign up to set email alerts
|

Community Surveillance of Respiratory Viruses Among Families in the Utah Better Identification of Germs-Longitudinal Viral Epidemiology (BIG-LoVE) Study

Abstract: Viral detection is often asymptomatic and occasionally prolonged, especially for bocavirus and rhinovirus. In clinical settings, the interpretation of positive PCR tests, particularly in young children and those who live with them, may be confounded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
191
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(219 citation statements)
references
References 34 publications
14
191
2
1
Order By: Relevance
“…RSV diagnostic research that does not use RT-PCR as a reference standard is therefore likely to overestimate RADT accuracy. However, using RT-PCR in the clinical setting, it has been observed that this method may detect asymptomatic or very low levels of viral shedding, which could sometimes be of questionable significance (103).…”
Section: Discussionmentioning
confidence: 99%
“…RSV diagnostic research that does not use RT-PCR as a reference standard is therefore likely to overestimate RADT accuracy. However, using RT-PCR in the clinical setting, it has been observed that this method may detect asymptomatic or very low levels of viral shedding, which could sometimes be of questionable significance (103).…”
Section: Discussionmentioning
confidence: 99%
“…Parents need encouragement and support when keeping track of the vaccination record of their children (Thorpe et al, 2016, Varkey et al, 2010). This may be particularly important in larger families with many children (Byington et al, 2015, Monto et al, 2014, Pearce et al, 2015, Amin et al, 2013, Oliveira et al, 2014). Current vaccination records however, are not designed to be used or understood by lay people.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of patients were admitted more than once during these six seasons, and if they had a repeat positive RSV molecular test, only unique admissions were included. It was thought that subsequent positive results on subsequent admissions could potentially represent prolonged viral shedding rather than new infection …”
Section: Methodsmentioning
confidence: 99%